Information technology usage, top management support and internal audit effectiveness - Mohammed Alkebsi; Khairul Azman Aziz (Penerbit Universiti Kebangsaan Malaysia, 2017)
There has been a marked increase in the global practice to focus on internal auditing as a mechanism to protectcompanies. With the advent of information technology, companies are presented with even more opportunity to improve the way they perform internal audit. However it is expected that such opportunity is dependent upon other factors such as management support. This research examines the moderating effect of top management support on the relationship between information technology usage and internal audit effectiveness. Questionnaires were sent to internal auditors in Yemeni private companies, with a total of 104 responses obtained. The study found a significant positive relationship between information technology usage and internal audit effectiveness. Similar result was obtained on the relationship between top management support and internal audit effectiveness. However the study found that top management supportdoes not moderate the relationship between information technology usage and internal audit effectiveness.